Launch your new products/services better, faster - Lynn, GS; Akgün, AE (Industrial Research Inst Inc, 2003)
OVERVIEW: By studying the practices of 117 new product teams from AT&T, Allied Signal, Digital Equipment, IBM, Motorola, and other companies, several factors were found that can help teams develop new products and services better and faster, with a greater probability of succeeding. Factors influencing new product success include: 1) teamwork, 2) market niche assessment, 3) cross-team communication, 4) clear project vision, and 5) limiting formal within team communications. Factors influencing speed-to-market include: 1) teamwork, 2) rapid prototyping, 3) team empowerment, 4) vision support, and 5) an aggressive launch deadline.
Keywords: Product